Vivaldi’s Bohemian Manuscripts - Everett, Paul (Journal of the Society for Musicology in Ireland, 2013)
The present article was originally published in Czech translation by Michaela Freemanová: ‘Vivaldiho bohemikální rukopisy’, Opus musicum, 44/3 (2012), 14-25. It concerns the several manuscripts - mostly autographs - of Antonio Vivaldi that appear to originate from Bohemia and the time of the composer’s visit, accompanied by his father Giovanni Battista Vivaldi, to ‘Germania’ in 1729-30. Besides three manuscripts of compositions with lute (RV 83, 85 and 93), whose association with Count Johann Joseph von Wrtby (Jan Josef z Vrtba, 1669-1734) had been recognized in the 1970s, there are eleven further manuscripts (of RV 155, 163, 186, 278, 282, 288, 330, 380, 473, 500 and 768) discovered to be of similar, putatively Bohemian provenance that survive in Vivaldi’s personal archive of music, now preserved in Turin. Through the examination of their paper-types and rastrographies (utterly distinct from those of the music papers Vivaldi typically used in Italy), a clear picture emerges of the near-contemporaneity and common origin of these fourteen manuscripts.